Redirecting Alzheimer Strategy Tracing Memory Loss to Self Pathology - Larrivee, Denis (IntechOpen, 2019)
It is fair to say that no brain disease occupies more research study today than Alzheimer's disease (AD). Among the many excellent reasons for this circumstance are the bleak prognosis and relentless progression; large cohorts of baby boomers entering an age of greatly increased cognitive risk; and spectacular advances in medical care that have prolonged lifespan. Often unattributed is the success of the research enterprise that has instilled confidence in AD's ultimate defeat. Yet, despite decades of intense research, AD remains poorly understood, an enigma amid a tide of neuroscientific advance. What these inconclusive results apparently call into question is an understanding of cognition that views it from the bottom up - the study of which is eminently suited by the scientific method - and that dispenses with a philosophy of biology concerned with how organismal properties operate, for which cognition is the medium. Culled from AD's new and old research archives, the chapters in this text accordingly lay out an argument for strategically new pathways that wander through cognition's global terrain and that may ultimately offer surer ground for AD treatment.